A Case Report of Cardiac Ascites in Morquio Syndrome Complicated by Pulmonary Hypertension - Gauri Patel; Olakanmi Joseph Deleawe (Annals of Internal Medicine: Clinical Cases)
Morquio syndrome, or mucopolysaccharidosis type IV (MPS IV), is a rare lysosomal storage disorder characterized by skeletal dysplasia and dysostosis multiplex. While primarily associated with skeletal manifestations, MPS IV can also affect systemic organs. Here, we present a case of a 64-year-old woman with MPS IVC who presented with cardiac ascites. The patient's disease course was characterized by idiopathic pulmonary hypertension to cor pulmonale and subsequent cardiac ascites formation. Utilizing paracentesis with cytology as well as an analysis of the patient's clinical history and disease progression, we provide insights into the interplay between Morquio syndrome and cardiac ascites.